2013
DOI: 10.1007/s00233-013-9548-x
|View full text |Cite
|
Sign up to set email alerts
|

On semigroups of endomorphisms of a chain with restricted range

Abstract: Let X be a finite or infinite chain and let O(X) be the monoid of all endomorphisms of X. In this paper, we describe the largest regular subsemigroup of O(X) and Green's relations on O(X). In fact, more generally, if Y is a nonempty subset of X and O(X, Y ) the subsemigroup of O(X) of all elements with range contained in Y , we characterize the largest regular subsemigroup of O(X, Y ) and Green's relations on O(X, Y ). Moreover, for finite chains, we determine when two semigroups of the type O(X, Y ) are isomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…For a finite chain X the ranks of the semigroups O(X, Y ) and OP(X, Y ) were determined by Fernandes, Honyam, Quinteiro, and Singha [6,7]. In [18], Tinpun and Koppitz studied the relative rank of T (X, Y ) modulo O(X, Y ).…”
Section: Introductionmentioning
confidence: 99%
“…For a finite chain X the ranks of the semigroups O(X, Y ) and OP(X, Y ) were determined by Fernandes, Honyam, Quinteiro, and Singha [6,7]. In [18], Tinpun and Koppitz studied the relative rank of T (X, Y ) modulo O(X, Y ).…”
Section: Introductionmentioning
confidence: 99%
“…Keprasit and Changphas [9] showed that if X is order-isomorphic to a subchain of Z, then OT (X) is regular. In [4], Fernandes et al described the largest regular subsemigroup of OT (X).…”
Section: Introductionmentioning
confidence: 99%
“…For a chain X , Mora and Kemprasit [14] gave a necessary and sufficient condition for OT (X, Y ) to be regular and determined all regular elements. Fernandes et al [4] characterized the largest regular subsemigroup of OT (X, Y ) .…”
Section: Introductionmentioning
confidence: 99%
“…Notice that J f is clearly an ideal of O(X). On the other hand, unlike the analogous set for T (X), J is not necessarily a J -class of O(X) (see [3]).…”
Section: Introductionmentioning
confidence: 99%